Hypertonic Saline Versus Mannitol for Traumatic Brain Injury: A Systematic Review and Meta-analysis With Trial Sequential Analysis. Issue 1 (January 2021) - Schwimmbeck, Franz; Voellger, Benjamin; Chappell, Daniel; Eberhart, Leopold
Abstract : Background: Mannitol and hypertonic saline are widely used to treat raised intracranial pressure (ICP) after traumatic brain injury (TBI), but the clinical superiority of one over the other has not been demonstrated. Methods: According to the PRISMA statement, this meta-analysis reports on randomized controlled trials investigating hypertonic saline compared with mannitol in the treatment of elevated ICP following TBI. The protocol for the literature searches (Medline, Embase, Central databases), quality assessment, endpoints (mortality, favorable outcome, brain perfusion parameters), and statistical analysis plan (including a trial sequential analysis) were prospectively specified and registered on the PROSPERO database (CRD42017057112). Results: A total of 12 randomized controlled trials with 464 patients were eligible for inclusion in this analysis. Although there was a nonsignificant trend in favor of hypertonic saline, there were no significant differences in mortality between the 2 treatments (relative risk [RR]: 0.69, 95% confidence interval [CI]: 0.45, 1.04; P =0.08). There were also no significant differences in favorable neurological outcome between hypertonic saline (HS) and mannitol (RR: 1.28, 95% CI: 0.86, 1.90; P =0.23). There was no difference in ICP at 30 to 60 minutes after treatment (mean difference [MD]: −0.19 mm Hg, 95% CI: −0.54, 0.17; P =0.30), whereas ICP was significantly lower after HS compared with mannitol at 90 to 120 minutes (MD: −2.33 mm Hg, 95% CI: −3.17, −1.50; P <0.00001). Cerebral perfusion pressure was higher between 30 to 60 and 90 to 120 minutes after treatment with HS compared with after treatment with mannitol (MD: 5.48 mm Hg, 95% CI: 4.84, 6.12; P <0.00001 and 9.08 mm Hg, 95% CI: 7.54, 10.62; P <0.00001, respectively). Trial sequential analysis showed that the number of cases was insufficient to produce reliable statements on long-term outcomes. Conclusion: There are indications that HS might be superior to mannitol in the treatment of TBI-related raised ICP. However, there are insufficient data to reach a definitive conclusion, and further studies are warranted. Abstract : Supplemental Digital Content is available in the text.